2016
DOI: 10.1080/15548627.2016.1239004
|View full text |Cite
|
Sign up to set email alerts
|

The ART and science of sperm mitophagy

Abstract: This article discusses the historical perspective and the new findings of autophagy and ubiquitin-proteasome system cooperation during the post-fertilization sperm mitophagy, a process that eliminates potentially damaged paternal mitochondrial DNA from an early embryo. New insight into the mechanism that promotes clonal, maternal inheritance of mitochondrial genes may be helpful for managing mitochondrial disease and infertility in humans, as well as reproductive performance and production traits in agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Of note, an additional group of nuclear proteins have been detected in this study, which, although not being associated to chromatin, is interesting to highlight. This is the case of the proteosomal proteins, since the proteosomal regulation is essential not only for the correct development of spermatogenesis, but also for the early events occurring at fertilization, which includes the process of sperm mitophagy, where potentially damaged paternal mitochondrial DNA is eliminated from the early embryo (Song et al 2016;Sutovsky 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, an additional group of nuclear proteins have been detected in this study, which, although not being associated to chromatin, is interesting to highlight. This is the case of the proteosomal proteins, since the proteosomal regulation is essential not only for the correct development of spermatogenesis, but also for the early events occurring at fertilization, which includes the process of sperm mitophagy, where potentially damaged paternal mitochondrial DNA is eliminated from the early embryo (Song et al 2016;Sutovsky 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For years, the maternal inheritance of the mitochondrial genome was considered as the result of a large dilution of paternal mitochondria contribution with respect to maternal load ( Song et al., 2016b ; Sutovsky and Song, 2018 ). Now we know that it relies on a combination of various active mechanisms that prevent the transmission of sperm mitochondrial genome.…”
Section: Introductionmentioning
confidence: 99%
“…Paternal mitochondria removal in zygote is a key step to ensure maternal inheritance of mitochondria. Both ubiquitin proteasome system and sperm mitophagy occurred during the elimination process [46][47][48][49]. Studies in the porcine zygote suggested that a combined action of SQSTM1-dependent autophagy and VCP-mediated ubiquitination of sperm mitochondrial proteins was responsible for sperm mitophagy [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Both ubiquitin proteasome system and sperm mitophagy occurred during the elimination process [46][47][48][49]. Studies in the porcine zygote suggested that a combined action of SQSTM1-dependent autophagy and VCP-mediated ubiquitination of sperm mitochondrial proteins was responsible for sperm mitophagy [47,48]. In Caenorhabditis elegans, LC3 was a key regulator to control the fate of sperm mitochondria via autophagosome targeted to the pericentrosomal area [50].…”
Section: Introductionmentioning
confidence: 99%